PERSIAN INTERPRETATION OF FINE ARTS - T. Toshboltaeva; Makhbuba Tojiboeva (American Journals, 2024)
Alisher Navoi's work, a classic example of Uzbek classic literature, is a great factor in the rise of the spiritual thinking of mankind. Not only the works of the poet in Turkish, but also his works in Persian, which are an incomparable example of the Zullisonayn tradition, are the cause of many studies. In this article, the poet's "Devoni Foni" Alisher Navoi's Persian heritage is looked at as an example of the analysis of his ghazals.
Keywords: Devon, ghazal, fine arts, proportion, talmeh, tashbeh, husni ta'lil.